2007
DOI: 10.1002/ar.20575
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography as a Tool for Measuring Morphogenetic Deformation of the Looping Heart

Abstract: Optical coherence tomography (OCT) was used to investigate morphogenesis of the embryonic chick heart during the first phase of looping (c-looping), as the heart bends and twists into a c-shaped tube. The present study focuses on the morphomechanical effects of the splanchnopleure (SPL), a membrane that has been shown to play a major role in cardiac torsion by pressing against the ventral surface of the heart. Without the SPL, rightward torsion (rotation) is delayed. The images show that compressive forces exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 39 publications
6
49
0
Order By: Relevance
“…Cross-sectional image stacks were reconstructed into 3D volumes and optically sectioned using Volocity (Improvision, Waltham, MA, USA). Time-lapse experiments were conducted with the custom-built OCT system described previously (Filas et al, 2007;Filas et al, 2008).…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional image stacks were reconstructed into 3D volumes and optically sectioned using Volocity (Improvision, Waltham, MA, USA). Time-lapse experiments were conducted with the custom-built OCT system described previously (Filas et al, 2007;Filas et al, 2008).…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…As described by Filas et al (Filas et al, 2007), the MATLAB routine gridfit was used to fit 2D surfaces through the set of marker coordinates to generate x(X, Y) and y(X, Y), which give the strain components in image coordinates by equation (1). Standard equations (Taber, 2004) were then used to transform these strains into components relative to an embryo coordinate system (X, Y) (Fig.…”
Section: Strain Analysismentioning
confidence: 99%
“…8 To date, the clinical applications for OCT in cardiology relate to coronary artery imaging. However in cardiac research, OCT has also been used to study the mechanical function of the embryonic mouse heart, 9 and the growth mechanics of the developing chick heart, 10 demonstrating that OCT can be used to investigate the relationship between cardiac structure and mechanical function. Also, two previous preliminary studies have shown that OCT can be used to recognize components of the cardiac conduction system, 4,11 which demonstrates that OCT can visualize distinct anatomical structures within the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the contrast in OCT images comes from the optical scattering properties of tissue, and thus OCT can capture valuable structural features by depicting tissue boundaries. For example, OCT has been frequently utilized to study embryonic heart morphogenesis during cardiac looping process to understand the etiology of congenital heart defects [19,20]. Recently OCT was used to image the neural tube closure which is a critical process in the development of neural tube defects [21].…”
Section: Introductionmentioning
confidence: 99%